The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1969
DOI: 10.1677/joe.0.0450001
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between the Uptakes of Radioactive Perchlorate and Iodide by Rat and Guinea-Pig Thyroid Glands

Abstract: SUMMARY Previous studies indicated that 36Cl-labelled perchlorate is concentrated by rat and rabbit thyroid gland. However, the extent of concentration of radioactive perchlorate in the gland was much less than that of iodide. Since perchlorate itself has a marked effect on anion transport in the thyroid and the specific activity of available [36C]perchlorate is very low, the stable anion as a carrier present in the injected radioactive perchlorate solution may affect the uptake of this radioactive com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1

Year Published

1974
1974
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 0 publications
2
24
1
Order By: Relevance
“…2, a mean cell count of 5.0 ϫ 10 5 /well and a mean thyroid cell volume of 3.73 pl (8), the calculated cell/medium ratio was 62 at the TSH-induced maximum uptake of perchlorate. Our results are consistent with studies of perchlorate uptake using 36 ClO 4 Ϫ in rats and guinea pigs showing that the isotope was concentrated in the thyroid tissue and that the concentration was TSH dependent (9,21).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…2, a mean cell count of 5.0 ϫ 10 5 /well and a mean thyroid cell volume of 3.73 pl (8), the calculated cell/medium ratio was 62 at the TSH-induced maximum uptake of perchlorate. Our results are consistent with studies of perchlorate uptake using 36 ClO 4 Ϫ in rats and guinea pigs showing that the isotope was concentrated in the thyroid tissue and that the concentration was TSH dependent (9,21).…”
Section: Discussionsupporting
confidence: 91%
“…This is in contradiction to previous studies showing that radiolabeled perchlorate was concentrated in thyroid tissue in vivo (9,10,32) and contrasts with the selectivity series based on physiological anion transport in thyroid tissue: , 34, 35). Recently, Dohan et al (14) published additional evidence of NIS-mediated active transport of perchlorate both in vivo and in vitro.…”
contrasting
confidence: 99%
“…Several kinetic studies of these compounds have been reported in the literature. However, the majority of these are reported as a ratio of tissue (e.g., thyroid) versus plasma concentration of radiolabeled iodide and/or perchlorate (Chow et al, 1969;Chow and Woodbury, 1970;Wollman and Reed, 1959).…”
Section: Discussionmentioning
confidence: 99%
“…Perchlorate is actively taken up by the thyroid gland and prevents iodide uptake into the thyroid, disrupting thyroid hormone synthesis and secretion (Anbar et al, 1959;Capen 1996;Chow et al, 1969;Wolff, 1998). Since perchlorate competitively inhibits iodide uptake into the thyroid, less iodide is available for organification.…”
Section: Discussionmentioning
confidence: 99%
“…At normal goitrogenic levels of these compounds, there is little uptake of the goitrogen into the thyroid (Chow et al 1969) therefore their activity must be upon the external membranes of the gland.…”
Section: Antithyroid Compoundsmentioning
confidence: 99%